2020
DOI: 10.3390/life10080153
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Sedentary Behavior, and Sleep Quality in Adults with Primary Hypertension and Obesity before and after an Aerobic Exercise Program: EXERDIET-HTA Study

Abstract: Background: The purposes of the study were to: analyze, by objective (accelerometry) and subjective (International Physical Activity Questionnaire, IPAQ) methodologies, the physical activity (PA) and sedentary behavior (SB) in healthy adults (HEALTHY, n = 30) and individuals with primary hypertension (HTN) and overweight/obesity (n = 218); assess the effects of an aerobic exercise intervention on physical activity (PA), sedentary behavior (SB), and sleep quality in the HTN group; and evaluate the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 54 publications
0
8
0
1
Order By: Relevance
“…The last group of interventions is a moderate-to-vigorous exercise routine, such as aerobic or ACSM guideline-based routine. All these studies reported similar results, such as an increase in PA, making participants more active [ 20 , 25 , 30 ]. A study by Feairheller et al showed that the carotid artery intima-to-media thickness was decreased by 6.4% and plasma nitric oxide level was increased by 76.6%, but there was no improvement in blood pressure.…”
Section: Discussionmentioning
confidence: 86%
“…The last group of interventions is a moderate-to-vigorous exercise routine, such as aerobic or ACSM guideline-based routine. All these studies reported similar results, such as an increase in PA, making participants more active [ 20 , 25 , 30 ]. A study by Feairheller et al showed that the carotid artery intima-to-media thickness was decreased by 6.4% and plasma nitric oxide level was increased by 76.6%, but there was no improvement in blood pressure.…”
Section: Discussionmentioning
confidence: 86%
“…Once the accelerometer and the daily activity record sheet have been collected, the data will be downloaded [ 26 ]. As this study is conducted with children, the originals will be converted to 60 seconds to calculate sleep [ 27 ] and to 5 seconds for daily PA [ 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it showed how this group of students were unaware of their condition and did not see themselves as obese and exhibiting signs of hypertension [43]. However, some studies suggest that it decreases the sedentary lifestyle by examining exercise programs and improves sleep quality in obese adults [44]. Engaging in a moderate exercise of at least 30 minutes in the week was sufficient to start lowering high blood pressure [43].…”
Section: Special Sense Coordinationmentioning
confidence: 99%